Development of an Enterovirus 71 Vaccine Efficacy Test Using Human Scavenger Receptor B2 Transgenic Mice - Imura, Ayumi; Sudaka, Yui; Takashino, Ayako; Tamura, Kanami; Kobayashi, Kyousuke; Nagata, Noriyo; Nishimura, Hidekazu; Mizuta, Katsumi; Koike, Satoshi (Journal of virology, 2020)
The development of new vaccines for EV71 relies on the availability of small animal models suitable for in vivo efficacy testing. Monkeys and neonatal mice have been used, but the use of these animals has several drawbacks, including high costs, limited susceptibility, and poor experimental reproducibility. In addition, the related ethical issues are considerable. The new efficacy test based on hSCARB2 Tg mice and virulent EV71 strains propagated in genetically modified cell lines presented here can overcome these disadvantages and is expected to accelerate the development of new EV71 vaccines. Enterovirus 71 (EV71) is a causative agent of hand-foot-mouth disease, and it sometimes causes severe neurological disease. Development of effective vaccines and animal models to evaluate vaccine candidates are needed. However, the animal models currently used for vaccine efficacy testing, monkeys and neonatal mice, have economic, ethical, and practical drawbacks. In addition, EV71 strains prepared for lethal challenge often develop decreased virulence during propagation in cell culture. To overcome these problems, we used a mouse model expressing human scavenger receptor B2 (hSCARB2) that showed lifelong susceptibility to EV71. We selected virulent EV71 strains belonging to the subgenogroups B4, B5, C1, C2, and C4 and propagated them using a culture method for EV71 without an apparent reduction in virulence. Here, we describe a novel EV71 vaccine efficacy test based on these hSCARB2 transgenic (Tg) mice and these virulent viruses. Adult Tg mice were immunized subcutaneously with formalin-inactivated EV71. The vaccine elicited sufficient levels of neutralizing antibodies in the immunized mice. The mice were subjected to lethal challenge with virulent viruses via intravenous injection. Survival, clinical signs, and body weight changes were observed for 2 weeks. Most immunized mice survived without clinical signs or histopathological lesions. The viral replication in immunized mice was much lower than that in nonimmunized mice. Mice immunized with the EV71 vaccine were only partially protected against lethal challenge with coxsackievirus A16. These results indicate that this new model is useful for in vivo EV71 vaccine efficacy testing. IMPORTANCE The development of new vaccines for EV71 relies on the availability of small animal models suitable for in vivo efficacy testing. Monkeys and neonatal mice have been used, but the use of these animals has several drawbacks, including high costs, limited susceptibility, and poor experimental reproducibility. In addition, the related ethical issues are considerable. The new efficacy test based on hSCARB2 Tg mice and virulent EV71 strains propagated in genetically modified cell lines presented here can overcome these disadvantages and is expected to accelerate the development of new EV71 vaccines.